Analysis of Digital Wallet Usage on Consumptive Lifestyle - Ramadhan, Naufal Dzaky; Fhatturohmah, Siska; Ramadhani, Sonia; Firmansyah, Esa (Journal of Islamic Economics and Business, 2023)
Many people, especially students, use e-wallets for daily transactions such as storing funds and purchasing daily necessities. The Prophet SAW also forbade the behavior of squandering or wastefulness in ablution using water, even though it was in the river. In fact, the lifestyle among students today is in stark contrast to the changes that occur, such as buying things that are not really needed at all. This is where the origin of a high lifestyle causes students to have irrational consumption abilities and tend to have consumptive behavior. Consumptive behavior that arises among students is caused by technological developments and in the development process of the individual himself. This research uses descriptive quantitative research methods with primary data from questionnaire results in the form of links from Google Forms, aiming to determine how much influence the use of digital wallets has on student lifestyles. The analysis of the effect of using digital wallets on the lifestyle of 2020 Islamic Economics students of UIN Sunan Gunung Djati Bandung obtained results that show an influence of the use of digital wallets on the lifestyle of 2020 Islamic economics students. This is evident from the number of 2020 Islamic economics students who use digital wallets for shopping activities, both for daily needs and just fulfilling desires.